Cloud accounting: strategic advantage for maximising Shareholder wealth in Nigeria’s pharmaceutical sector - Ikwuo, Ama Kalu; Ukoha, Adaku Chinonyerem; Nworie, Gilbert Ogechukwu (Goodwood Publishing, 2025)
Purpose: This study examines the effect of cloud accounting on shareholder wealth maximization among listed pharmaceutical firms in Nigeria. Specifically, this study examined the effect of cloud accounting software usage and cloud accounting software intensity on the return on equity of listed pharmaceutical firms in Nigeria. Methods: An ex post factor research design was used in this study. A sample size of Five listed pharmaceutical firms in Nigeria were purposively sampled from a population of seven (7). Secondary data were sourced from the annual reports of firms from 2014 to 2023, covering a ten-year period. In addition to the descriptive analysis, model diagnoses such as multicollinearity, autocorrelation, heteroskedasticity, and normality tests were conducted to validate the model. Hypotheses testing was performed using estimates from robust least-squares regression at the 5% significance level. Results: The findings indicate that while cloud accounting software usage significantly improves the return on equity of listed pharmaceutical firms in Nigeria (p-value = 0.0056), cloud accounting software intensity negatively affects the return on equity of listed pharmaceutical firms in Nigeria (p = 0.0147). Limitations: This study’s limitation is based on the fact that the findings cannot be generalized to other sectors apart from the Nigerian pharmaceutical sector. Contributions: Based on the findings of the study, pharmaceutical firms in Nigeria should enhance their investment in cloud accounting software by regularly training their finance teams on the effective use of these systems to maximize the benefits of cloud accounting to improve shareholder value.